Featured Cover. Issue 1 (19th January 2021) - Zhao, Jingjing; Yuan, Fang; Fu, Feng; Liu, Yi; Xue, Changhu; Wang, Kangjun; Yuan, Xiangjun; Li, Dingan; Liu, Qiuwu; Zhang, Wei; Jia, Yi; He, Jianbo; et al.
Abstract: The cover image is based on the Original Paper Blood pressure variability and outcome in acute severe stroke: A post hoc analysis of CHASE—A randomized controlled trial by Jingjing Zhao et al., https://doi.org/10.1111/jch.14090 .